Prospects for the application of unified tax payment in the digital economy - E. L. Gulkova; M. V. Karp; M. V. Tipalina (Вестник университета, 2022)
The unified tax payment is to simplify the payment of taxes, reduce the time for filling out payment documents and reduce the number of mistakes in them. The purpose of the paper is to analyze the use of the unified tax payment from the perspective of its impact on tax administration and taxpayers’ activities.In this article, the authors set the following tasks: to determine the procedure for paying the unified tax payment; to assess the possibility of expanding the practice of its application and identify possible problems.The data on the voluntary remittances of the unified tax payment by physical persons during the period from 2019 to 2022 is presented. A critical analysis of the draft laws No. 46702-8 «On Amendments to Part One and Part Two of the Tax Code of the Russian Federation (in terms of improving the procedure for paying taxes) and No. 20281-8 «On conducting an experiment to establish a special tax regime «Automated simplified taxation system» is carried out. The paper highlights the main problems which companies may face if the institution of the «unified tax payment» is applied on a mandatory basis and identifies the possible ways to solve them. The authors’ recommendations and conclusions can be used in the development of conceptual provisions of tax policy.